PLANETARY SYSTEMS OF THE GALAXY - Evsukov, N. N.; Zakhozhaj, V. A.; Psaryov, V. A. (Одеські астрономічні публікації, 2017)
Definition of planets, relative contents of planetary systems in Galaxy, and main results of searching for them are adduced. It is supposed to distinguish four types of planets accordingly their inner substance composition: hydrogenous-helium (H2 , He, Ne), ice (H2O, CH4, NH3 and their cluster tree, also N2 and Ar), silicate, or metallic (alligations of Fe with Ni, Co, Cr) ones. Hydrogenous-helium compositions of planets are the most possible. But existence of two metallic (or metallic and silicate) and one ice planet in pulsar systems are suspected.